Addition of eptifibatide and manual thrombus aspiration to ticagrelor does not improve long-term survival after STEMI treated with primary PCI - Călburean, Paul-Adrian; Grebenișan, Paul; Nistor, Ioana-Andreea; Pal, Krisztina; Vacariu, Victor; Drincal, Reka-Katalin; Ion, Alissa Anamaria; Adorján, István; Oltean, Tiberiu; Hadadi, László (Frontiers in Pharmacology, 2024)
Current guidelines recommend that glycoprotein IIb/IIIa inhibitor (GPI) and manual aspiration thrombectomy should not be routinely used in patients with ST-segment elevation myocardial infarction (STEMI) treated by primary percutaneous coronary intervention (pPCI), although dedicated studies are lacking. The aim was to examine the impact of combined usage of potent P2Y12 inhibitor, GPI, and manual aspiration thrombectomy on long-term survival after STEMI.All STEMI patients treated by pPCI in a tertiary center that have been included prospectively in the local PCI Registry between January 2016 and December 2022 were analyzed in this study. Patients were excluded if they required oral anticoagulation or bridging between clopidogrel or ticagrelor during hospitalization.A total of 1210 patients were included in the present study, with a median follow-up of 2.78(1.00-4.88) years. Ticagrelor significantly reduced all-cause and cardiovascular-cause mortality (HR=0.27 [0.21-0.34], p<0.0001, and HR=0.23 [0.17-0.30], p<0.0001, respectively).Eptifibatide significantly reduced all-cause and cardiovascular-cause mortality (HR=0.72 [0.57-0.92], p=0.002, and HR=0.68 [0.52-0.89], p=0.001, respectively). Manual thrombus aspiration had no significant effect on both all-cause and cardiovascular cause mortality. In multivariate Cox regression, all-cause mortality was reduced by ticagrelor, while eptifibatide or manual thrombus aspiration had no significant effect. However, cardiovascular-cause mortality was reduced by both ticagrelor and eptifibatide, while manual thrombus aspiration had no significant effect.Ticagrelor consistently reduced cardiovascular and all-cause mortality, while eptifibatide reduced only cardiovascular mortality. Manual thrombus aspiration provided no long-term benefit. Our findings support current guidelines recommendation that GPI and manual aspiration thrombectomy should not be routinely used in STEMI treated by pPCI.